2022
DOI: 10.1002/iub.2655
|View full text |Cite
|
Sign up to set email alerts
|

Cancer combination therapies by silencing of CTLA‐4, PD‐L1, and TIM3 in osteosarcoma

Abstract: Osteosarcoma (OS) is the most common orthopedic neoplasm, with a high metastasis rate and a dismal prognosis despite surgery and chemotherapy.Immunotherapies have offered cancer patients a ray of optimism, but their impact on OS has been disappointing. The objective of this study is to assess the effect of mono, dual, and triple combinations of CTLA-4, PD-L1, and TIM3 blockade on OS cell viability, apoptosis, and migration. The MG-63 and U-2 OS cell lines were transfected with mono, dual, and triple combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Accumulating evidence suggests that the interaction between TIM-3 and PD-1 synergistically suppresses T cell responses, promoting T cell exhaustion in sepsis ( 55 ). Furthermore, the co-expression of TIM-3 and CTLA-4 has been associated with suboptimal T cell function and worse clinical outcomes in sepsis patients ( 56 ). These interactions underscore the importance of comprehensive studies on multiple immune inhibitory pathways in sepsis, paving the way for novel combination immunotherapy strategies.…”
Section: The Role Of Tim-3 In Sepsismentioning
confidence: 99%
“…Accumulating evidence suggests that the interaction between TIM-3 and PD-1 synergistically suppresses T cell responses, promoting T cell exhaustion in sepsis ( 55 ). Furthermore, the co-expression of TIM-3 and CTLA-4 has been associated with suboptimal T cell function and worse clinical outcomes in sepsis patients ( 56 ). These interactions underscore the importance of comprehensive studies on multiple immune inhibitory pathways in sepsis, paving the way for novel combination immunotherapy strategies.…”
Section: The Role Of Tim-3 In Sepsismentioning
confidence: 99%
“…As well, experiments on solid tumor-bearing mice models demonstrated that triple knockdown of transcription factors involved in the expression of inhibitory receptors such as NR4A1, NR4A2, and NR4A3 enhance anti-tumor activity and survival of CAR T-cells ( 237 ). Likewise, the TGF-β signaling cascade induces suppression of T-cell expansion, effector function, and migration through upregulation of the inhibitory receptors PD-1 and T-cell immunoglobulin and mucin domain 3 (TIM-3) ( 238 ), which have been shown to implicate in various solid tumors development and progression ( 239 ). This has prompted researchers to engineer CAR T-cells to co-express a bispecific protein of anti-PD-1 fused with a TGF-β trap to concurrently hinder the PD-1/PD-L1 axis and the TGF-β signaling cascade ( 233 ).…”
Section: Counterstrategies For Obstacles Of Car T-cell Therapymentioning
confidence: 99%
“…The immune checkpoint ligand PD-L1 has been found to be overexpressed in a variety of solid tumors [ 199 ]. PD-L1 binds to its receptor PD-1, and blocking it has shown therapeutic potential in cancer therapy [ 200 ]. However, when PD-L1 blockade is combined with optimal dose IL-12 delivery, it induces a synergistic effect of enhancing anti-tumor immunity in cancer patients [ 201 ].…”
Section: Msc-based Delivery Of Oncolytic Adenovirus (Oads)mentioning
confidence: 99%